Mentorship and Startup Growth: The Role of Social Capital Dimensions in Entrepreneurial Ventures - Shrestha, Rojan (Journal of Development and Administrative Studies, 2025)
Start-ups are at the core of economic growth which we see in product development and innovation they bring to the global stage. But the hard truth is that 70% of startups fail worldwide which is why we need to assist them with strategies that will enhance their growth and sustain them. Startups are most likely to perform their operation in the belief of their own expertise. Yet adequate mentorship programs could be a good idea to polish such entrepreneurial ventures. A deep analysis of start-ups, mentorship, and their relation can enhance entrepreneurial education and support start-ups to overcome failure. This study incorporates Social Capital theory to analyze coping drivers to address market challenges. Cognitive, relational, and structural dimensions of social capital theory facilitate knowledge sharing, trust, and collaboration among individuals. Through mentoring relationships, entrepreneurs gain expertise, strategic insight, and emotional support, which enhance their capacity to overcome business challenges and expand their ventures. Structured questionnaires were distributed to 120 employees, founders and co-founders of start-ups to ascertain their view towards mentorship. A causal comparative study was employed. In accordance with social capital theory, mentorship strengthens entrepreneurs’ access to valuable resources through networks and relationships. Key findings reveal that entrepreneurs require support from experts where close mentorship being priority. This indicates that improved entrepreneurial efficiency through mentorship can trigger growth in start-ups and enhance performance of venture in Nepal.